CMOS circuits for passive wireless microsystems - Yuan, Fei 1964- (Springer, 2011)
CMOS Circuits for Passive Wireless Microsystems by Fei Yuan this book provides a comprehensive treatment of the design principles and implementation of CMOS circuits and systems for passive wireless microsystems. Major subjects covered in the book include: passive wireless microsystems, radio-frequency power harvest, data encoding, modulators and demodulators, low-power precision voltage references, clock generation and calibration, and low-power analog-to-digital converters. This book's contents serve as an exhaustive survey of recently published work in this fast evolving field, and are presented with an emphasis on both the design principles and in-depth comparison of the pros and cons of the designs. This book provides the state-of-the-art of CMOS circuits for passive wireless microsystems. It is an invaluable resource for graduate students, IC design engineers and researchers working in this fast-evolving field. ?Systematically presents CMOS circuit implementation of passive wireless microsystems, providing both theoretical background and practical implementation examples; ?Provides in-depth comparison of the pros and cons of different topologies of CMOS circuits for passive wireless microsystems; ?Focuses on highly-applied topics, such as radio-frequency power harvesting, voltage multipliers, ultra-low power current and voltage references for passive wireless microsystems, low-power ASK demodulators for passive wireless microsystems, remote clock calibration of passive wireless microsystems, and low-power analog-to-digital converters.